Design of mucoadhesive gellan gum and chitosan nanoparticles intended for colon-specific delivery of peptide drugs - Cardoso, Valéria Maria de Oliveira [UNESP] (2021)
Nanotechnology has been widely used in the development of polymer nanocarriers for the oral delivery of biomolecules. The use of nanostructured systems can improve drug delivery and help to overcome the disadvantages of the oral administration of peptides. Nanoparticles (NPs) based on gellan gum (GG) and chitosan (CS) blends were prepared through polyelectrolyte complexation. The influence of pH on the zeta potential (ZP) of polymers allowed the selection of pH 5.0 as the most suitable pH for the complexation of polyelectrolytes. The effects of the polymer mass ratio and addition order on the formation and physicochemical properties of the NPs were evaluated. All NPs showed high positive ZP (> + 30 mV), which ensures electrostatic stability. The order of addition of the polymers influenced the particle size. Nanoscale structures (575.30–974.60 nm) were formed when GG (0.5–3 mg) was dripped into the CS dispersion (0.75–4.5 mg); however, when CS was dripped in the GG dispersion, particle aggregation occurred (sizes >5000 nm). Polymyxin B (PMB) nanoencapsulation reduced the particle size, mainly at low GG mass (1.5 mg). The PMB–polymer interactions were detected by Fourier transform infrared spectroscopy. The X-ray diffraction data indicated the formation of more organized structures with a higher degree of crystallinity. Scanning electron microscopy revealed spherical and uniform NPs. The mucoadhesive capability of the NPs was also demonstrated. The NP2_1 and NP2_3 released the lowest amount of drug in HCl 0.1 N (pH 1.2) (<29%), and the drug release rate was controlled in a phosphate buffer 0.1 M (pH 6.8) (<60%). The important findings of this study suggest that nanocarriers with tailored properties may be utilized to overcome the challenges of oral administration of peptides, such as PMB, contributing to the advances in the search for alternatives to the oral administration of PMB.